CLINICAL FEATURES OF TYPE 2 DIABETES DIFFERENT PHENOTYPES - O. Yu. Shabelnikova; I. A. Bondar (Сибирский научный медицинский журнал, 2020)
Objective of the study was to investigate clinical features of phenotypic variants of type 2 diabetes mellitus (T2DM) for personalization of hypoglycemic therapy. Material and methods. 2085 patients with T2DM (637 men and 1148 women), mean age 58.7 ± 6.9 years, duration of diabetes 7.8 ± 6.5 years; level of glycated hemoglobin (HbA1c), creatinine, urea,  total cholesterol, triglycerides, low (LDL) and high density lipoprotein, uric acid, ALT, AST, insulin, C-peptide, microalbuminuria were examined. Depending on the level of C-peptide and the index of HOMA-IR, patients were divided into 3 groups: group of insulinopenic phenotype (n = 250, 12 %), group of classical phenotype (n = 1605, 77 %) and group of hyperinsulinemic phenotype (n = 230, 11 %). Results. Patients with hyperinsulinemic phenotype differed from patients with classical and insulinopenic phenotype by later age of onset of diabetes (52.3 ± 8.1 years), high body mass index (BMI; 37.2 ± 7.4 kg/m2), blood LDL (3.38 ± 1.08 mmol/l) and creatinine level and frequency of chronic kidney disease (39.1 %). Patients with the insulinopenic phenotype had less diabetes duration (48.3 ± 7.9 years), a lower BMI (31.1 ± 6.3 kg/m2), higher blood glucose and HbA1c level and the frequency of diabetic polyneuropathy. Patients with the classic phenotype had a higher frequency coronary artery disease (20.8 %) compared to other phenotypes. Patients with insulinopenic phenotype on hypoglycemic tablets and patients with hyperinsulinemic phenotype on insulin therapy did not have HbA1c less than 7 %. Conclusions. To personalize therapy, the phenotypic variant of type 2 diabetes should be considered, with a study of the level of C-peptide, insulin and the calculation of the HOMA-IR insulin resistance index to determine the phenotype.